Penerapan Model Pembelajaran Cooperative Learning Picture and Picture untuk Meningkatkan Hasil Belajar dan Kedisiplinan PKn Kelas I SD - Anuhoni, Rachajeng; Wulandari, Murfiah Dewi; Rahayu, Ratna Puji (FONDATIA, 2024)
This research aims to improve learning outcomes using the cooperative learning model of PKn subject matter, understanding the rules of class I elementary school of Wirogunan 03 Kartasura District Sukoharjo Regency, and to improve discipline using the cooperative learning model of cooperative learning pictures and pictures in the PKn subject matter, understanding the rules of class I elementary school of Wirogunan 03 Kartasura District Sukoharjo Regency. This type of research is classroom action research (CAR). In the implementation of cycle I, it showed an increase in learning outcomes by 62.5%, and in the implementation of cycle II, it increased to 87.5%. The level of discipline of grade 1 students increased, from 75% in cycle I to 95% in cycle II. From the research results, it can be concluded that the implementation of the cooperative learning picture and picture model is successful and effective in improving student learning outcomes and discipline in PKn subjects, especially in understanding the rules, at Wirogunan 03 State Elementary School, Kartasura, Sukoharjo Regency.